Calculated Electronic Energy Loss of Heavy Ions at Low Energies in LR-115, Kapton, SiO2, and Al2O3 Amorphous Materials - J. El Asri; O. El Bounagui; N. Tahiri; A. Chetaine; H. Erramli (Atom Indonesia, 2021)
The electronic stopping powers of LR-115 and Kapton polymeric foilshave been estimated, using Monte Carlo simulations, for 9Be, 11B, 12C, 14N, 16O, and 35Cl ions covering the energy range ~0.1-1.0 MeV/n. Comparison of stopping power based on Lindhard, Scharff, and Schiott (LSS) theory with the corresponding values obtained by SRIM and MSTAR codes in LR-115 and Kapton polymeric foils illustrate a significantly large deviations. However, a semiempirical equation has been proposed here and tested for better stopping power calculations at low-energy regime in the domain of LSS theory for Z = 4-8 ions across materials. Furthermore, the electronic energy losses for 9Be and 16O ions in SiO2 and Al2O3, respectively, have been calculated in the energy range of ~0.1-1.0 MeV/n. The calculated stopping powers exhibit up to 10 % deviation from the experimental values and MSTAR data.